Identifikasi Kualitas Air Sungai Kalimas Menggunakan Pemodelan QUAL2kw - Muhammad Rizal Pambudi; Yayok Suryo Purnomo; Naniek Ratni JAR; Okik Hendriyanto Cahyonugroho (Yayasan Literasi Sains Indonesia, 2022)
“The Kalimas River is a river that runs across The Surabaya City. This river is a tributary of the Surabaya River. There are few functions of this river, namely as one of the main drainage channels, fishing locations. From the water quality data collected by DLH Surabaya City, Kalimas river water quality is included in class III. The 2020-2025 Regional Medium-Term Development Plan states that the Kalimas River has function as river transportation and tourism facilities. Meanwhile, in Permen LH No. 5 of 2021, class II rivers can be the only one used as tourism facilities. Because of this, efforts or studies are needed so that the river can make up to class II standards. , what is the level of contamination in the water body, it is also necessary to know the maximum capacity level of the Kalimas River. The first steps is to identify the quality of the Kalimas River using the QUAL2KW Modeling method, with 3 skenarios to take into account the calibration of each parameter, parameter values ​​in the coming year, and the natural conditions of the Kalimas River without pollutant load input. The results of the study show that currently the Kalimas River is in class III and has a pollution carrying capacity for BOD parameters of 1.29 kg/day to 7.29 kg/day; the COD parameter is 0.48 kg/day to 5.62 kg/day; the TSS parameter is 257.12 to 257.99 kg/day.”